ChemInform Abstract: Stereoselectivity of 6‐Exo Cyclization of α‐Carbamoyl Radicals. Issue 31 (14th July 2016) - Song, Liyan; Fang, Xinqiang; Wang, Zijia; Liu, Kun; Li, Chaozhong
Abstract: The BEt3 /O2 ‐initiated iodine‐atom‐transfer radical cyclization reactions of substituted N‐(but‐3‐en‐1‐yl)‐N‐(tert‐butyl)‐2‐iodoalkanamides furnishes predominantly 3, 4‐cis, 4, 5‐trans, or 4, 6‐trans substituted δ‐lactams.